Fontes de informação das adolescentes e o diálogo com pais e parceiros sobre DST/AIDS/Anticoncepção - Lima, Márcia Santana (2013)
This work aimed to identify the existence of dialogs between parents and daughters and between students from a public school in the countryside of Sao Paulo State and their partners. The sample was composed by 159 adolescents from female gender with ages between 11 and 19 years old, whose ages match with the adolescence period according to the literature. They were invited to participate on the study and their parents have authorized them by signing the TCLE (Informed Consent).As instruments for data collecting there was used questionnaire, translated, adapted and validated by the team of researchers from Universidade Federal do Ceará, in 2011. The adapted questionnaire used in this work is named Parent-Adolescent Communication Scale – PACS, which focus on the relation between adolescents and their sexual partners, and was the guide resource for this work. The results were evaluated in quantitative and descriptive manner. It does exist dialogue inside the family concerning the theme. The maternal figure is more influent and the father express more distance from the topic. The school comes in second level of providing information and demonstrates its essential role in the prevention of STD and contraception orientation. It was highlighted low family income, as 48% from the adolescents declared that the family earned between 1 and 2 of the minimum wage per month. It was revealed a great number of people living in the same home. As for race and skin colour, 33 % declared to be mulatto and 44,4% declared to be white. From the group 61% live with biparietal families and 25% get income from work. Concerning the behaviour and communication about sexual and reproductive health, 30% told to have had the first period when they were 12 years old, 55,3% had information before the first period came, and 56,6% had information about sexual relationship with their maternal figure and the paternal figure was mentioned only by 1,9%. As for pregnancy, 64,2% referred to the mother as the most important source of information, and 67,5% declared to have had their first sexual relationship between 14 and 16 years old, and 23,3% related the mother knew everything, and 83,7% declared to have had their first sexual relationship with a boyfriend. The average age of partners was between 16 and 18 years old. From the adolescents, 74,4% declared to talk with their partners about the theme. It can be concluded that the dialogue between adolescents and their families exists, highlighting the maternal figure. It was verified that the father does not participate effectively from dialogues about the theme and the healthcare services was too little mentioned as information resources about STD/AIDS, pregnancy and first period. Keywords: Adolescent Health; Sexually Transmitted Diseases; Contraception; Communication; Family.